Mass movement of individuals at Carara National Park - Barquero Arroyo, Marco David (2021)
The video shows the movement of individuals of the Green-and-Black Poison Dart Frog, Dendrobates auratus, under rainy conditions. The filmed individuals moved close to the researchers and in close proximity of conspecifics. Parque Nacional Carara, Costa Rica